Edukasi Perilaku Hidup Bersih Sehat (PHBS) Pada Siswa Sekolah Dasar - Rici Gusti Maulani; Nuari Andolina; Triveni Triveni (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2024)
Clean and Healthy Living Behavior (PHBS) is all health behavior carried out with awareness so that family or family members can help themselves in the health sector and can play an active role in health activities in the community (Proverawati & Rahmawati 2016). Some students at SD 003 Bengkong, Batam City still don't know what Clean and Healthy Living Behavior (PHBS) is, it can be seen from the fact that some of these students do not maintain personal and environmental cleanliness. PHBS students' knowledge of washing hands, using toilets, exercising regularly, shampooing hair will prevent diarrhea. This research was conducted with the aim of finding out the level of knowledge of class VI students at SD 003 Bengkong, Batam City regarding PHBS. The aim of this Community Service is to determine the knowledge of class VI students. This activity is carried out by providing education using leaflets and electronic media. The methods used are lectures, questions and answers and quizzes. The evaluation results of this activity are an increase in students' knowledge of Clean and Healthy Living Behavior (PHBS).